Mechanical Ventilation - Gutiérrez Muñoz, Fernando (2011)
Mechanical ventilation (MV) is a therapeutic resource of life support, which has been instrumental in improving survival in critically ill patients, especially those suffering acute respiratory failure (ARF); A better understanding of the pathophysiology and recent advances in computer technology have improved mechanical ventilators facilitate the treatment of these patients. This article aims at a practical description of the MV, involving an explanation of the mechanical ventilator, their components, their functions and physiological effects produced by subjecting a patient to the MV; also outlines the indications, how and why program the different parameters of media, including a graphic explanation of the most frequently used ventilatory modes and multimodal monitoring allows us to optimize the management individually for each situation; also details the most common complications and succinctly describes the weaning or discontinuation of the MV, also reviewed the details of the transport of patients with ventilatory support and reviewed the most used drugs for sedation and analgesia.